Sport4STEM - Englén, Alba; Enström, Ella; Eriksson, Wilma; Gindahl, Emelie; Nordanstig, Louise; Wallin, Emma (My University, 2025)
STEM, an acronym for Science, Technology, Engineering, and Mathematics, is currently facing a significant shortage of competence, posing challenges that affect society at large. At the same time, children from socioeconomically disadvantaged backgrounds remain underrepresented in higher education. In this project a concept was created with the purpose to spark interest in STEM-subjects among children, with a particular focus on those from socioeconomically disadvantaged areas. By using sports as a tool to promote STEM, an 8-week program was developed, featuring weekly activities, with a clear timeline and detailed activities. The activities have been tested and show a clear connection between sport and STEM in an accessible and engaging way for the target group. The project followed an iterative design process, which partly included problem identification through data collection methods such as benchmarking, interviews, and a workshop. Based on the insights gathered, a comprehensive list of user needs and criteria was formulated. Subsequently, ideas were generated, tested, and evaluated. The final concept is presented in the form of a website, coupled with visual materials intended to illustrate the activities. These illustrations contain descriptions of the activities and required material. The concept was evaluated in collaboration with children and teachers in a school. Two key insights emerged as critical success factors, regardless of the specific activities selected: the importance of relationship-building and experiential learning. These findings were consistently highlighted in interviews, the workshop, and literature reviews. The program is designed as a leisure activity outside school hours. Although similar initiatives exist, the explicit focus on socioeconomically disadvantaged areas, the integration of sports and STEM, and the structured framework of the concept appear to be unexplored areas with high potential, according to the results from benchmarking and interviews. Based on the findings, three main conclusions can be drawn. First, the program stands out in its unique approach to integrate STEM subjects with sports, in which great economic resources are not required. Second, strong and competent leadership plays a crucial role in raising an interest within STEM-subjects among children, and fostering long-term relationships between leaders and youth. Therefore, leaders should be carefully selected and capable of leading a variety of activities to promote trust, a sense of safety and belonging. Lastly, the program shows great potential for success, with the capacity to make a meaningful impact on individual children, as well as the broader society and ultimately even on a global scale.